PEMETAAN RISIKO SISTEMATIS & PEMBENTUKAN PORTOFOLIO OPTIMAL SAHAM INDEKS LQ45 DENGAN MODEL INDEKS TUNGGAL - Chloe, Paquita Maria Angelina; Hascaryani, Tyas Danarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Systematic risk is one of the most important aspects of portfolio investment. The market uncertainty has led to systematic risk changes, especially during the Covid-19 outbreak. Systematic risk might not be diversified but it is possible to avoid high systematic risk by choosing low systematic risk stocks. By knowing the beta (systematic risk) distribution, investors can choose low systematic risk stocks for their portfolio. The aim of this research is to build optimal portfolio by considering systematic risk distribution among LQ45 index. This research found that the Financial sector has the highest systematic risk while the Consumer Goods sector has the lowest systematic risk. This study also finds that portfolio risk can be reduced by choosing low-systematic risk stocks.